Reubicación y expectativas de modernidad: el caso de las familias campesinas de Yanacona y el proyecto Aeropuerto Internacional de Chinchero (Cusco) - López Aguilar, Marcos (2019)
In December 2012, the Regional Government of Cusco expropriated lands owned by the rural community of Yanacona in order to allow the construction of the International Airport at Chinchero (Cusco). In addition to the payment of economic compensation, it undertook to relocate the population affected by the expropriation process. The article focuses on analyzing the resettlement process of the affected population and their expectations of modernity. The analysis shows that Regional Government did not ensure the mitigation of negative impacts of an involuntary resettlement process.Indeed, it was limited to financial compensation for the houses that the affected families would lose. Consequently, Regional Government did not ensure the reduction of the negative impact generated by a relocation. This was possible mainly due to the community’s expectations of modernity associated with the project.